2020
DOI: 10.5194/wes-5-1315-2020
|View full text |Cite
|
Sign up to set email alerts
|

Optimal closed-loop wake steering – Part 1: Conventionally neutral atmospheric boundary layer conditions

Abstract: Abstract. Strategies for wake loss mitigation through the use of dynamic closed-loop wake steering are investigated using large eddy simulations of conventionally neutral atmospheric boundary layer conditions in which the neutral boundary layer is capped by an inversion and a stable free atmosphere. The closed-loop controller synthesized in this study consists of a physics-based lifting line wake model combined with a data-driven ensemble Kalman filter (EnKF) state estimation technique to calibrate the wake mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 82 publications
1
44
0
Order By: Relevance
“…This also includes added turbulence caused by nearby turbine operation to more accurately calculate the rate of wake expansion. Many other linear-flow models use a constant parameter that defines the rate of wake expansion and has no dependency on the operating conditions of the turbine (Jensen, 1983). From the concepts of Niayifar and Porté-Agel (2015), the Gaussian model relates the rate of wake expansion in the lateral and vertical directions directly to the ambient turbulence intensity present at a turbine and two tuned parameters, k a = 0.38371 and k b = 0.003678:…”
Section: Atmospheric Stabilitymentioning
confidence: 99%
“…This also includes added turbulence caused by nearby turbine operation to more accurately calculate the rate of wake expansion. Many other linear-flow models use a constant parameter that defines the rate of wake expansion and has no dependency on the operating conditions of the turbine (Jensen, 1983). From the concepts of Niayifar and Porté-Agel (2015), the Gaussian model relates the rate of wake expansion in the lateral and vertical directions directly to the ambient turbulence intensity present at a turbine and two tuned parameters, k a = 0.38371 and k b = 0.003678:…”
Section: Atmospheric Stabilitymentioning
confidence: 99%
“…For wake model-based closed-loop control (e.g. the method proposed by Howland et al (2020) 21 ), the goal is to calculate the optimal yaw set-points for the wind farm over the finite control update time horizon. In both approaches, the set-point optimization can be considered over wind condition probabilities.…”
Section: Yaw Set-point Optimization Under Model Parameter Uncertaintymentioning
confidence: 99%
“…Wake model parameters have been tuned using LiDAR field data 17 and neutral ABL LES flow fields 18 . Recent work has optimized the wake model parameters using only wind farm power data and analytic gradients 5 , a novel calibration procedure 19 , genetic algorithms 20 , and Kalman filtering 21 and demonstrated that assimilating operational wind farm data into the wake model improves its predictive capability. Zhang & Zhao (2020) 22 used sampling to approximate the Bayesian posterior distributions of wake model parameters given LES data as the ground truth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be pointed out that, as an alternative to the robust design of yaw offset set-points that are valid for a range of conditions, one could consider adaptive solutions in which the yaw set-points are updated in real-life based on (estimates of) the actual operating conditions. Such an approach is pursued in Howland et al (2020), where a gradient ascent algorithm updates the yaw offsets at each iteration based on analytically derived gradients for the lifting line wake model, the parameters of which are estimated online.…”
Section: Introductionmentioning
confidence: 99%